The Initial Antibacterial Activity Tests of Pliek U Oil and Pliek U: an Acehnese Traditional Food - Nurliana Nurliana; Mirnawati Sudarwanto; Lisdar I. Sudirman; A. W. Sanjaya (Jurnal Kedokteran Hewan, 2008)
This initial research was intended to detect antibacterial activity of pliek u oil and pliek u. Pliek u oil consist of minyeuk simplah (MS) and minyeuk brok (MB), Pliek u consist of two kinds of solid waste namely wet pliek u (Ap1) and dry pliek u (Ap2). Pliek u was methanol extracted at concentration 10% (w/v). Pliek u oil and methanol extract of pliek u were evaluated for their antibacterial activity, against Bacillus subtilis and four strains of Enterophatogenic Escherichia coli (EPEC) employing agar disc diffusion method. No antibacterial activity was shown by MS. The MB exhibited a little effect 1-2 mm against bacterial tests. The results demonstrated that the higher antibacterial activity was shown by dry pliek u compare with wet pliek u with the inhibition zones from 6.67-10.33 mm and 6.00-7.33 mm respectively.